Social Behaviour di Pesantren Salaf - Arif, Mohamad (Asketik: Jurnal Agama dan Perubahan Sosial, 2017)
Salaf pesantren is an institution that is still strongly bound by old traditions. By inheriting and maintain continuity of Islamic tradition developed by scholars from time to time indefinite periodesasinya, has elements which include clerics, students, cottage / hostel, mosque, recitals of classical texts / yellow book, applying the method bandongan, sorogan, wetonan, principled firmly on Islamic education material. Pesantren Salaf urgently need progress in science and technology. Pesantren Salaf there are many who “failed” to preserve its own leadership weights, weak in preparing a “succession” Kyai guardians comparable with the foregoing, let alone exceeded. Answering the needs of the era, schools Salaf open formal educational institutions. Sensitivity pesantren Salaf against the phenomena that appear in the society is a social concern and reflexive owned even are characteristic. So that the aspirations of the people making the boarding school received the development and advancement of science and technology. The real step taken is establishing formal educational institutions from kindergarten through college. The character of a scholar is asceticism and totality. On the other hand, people still expect the efficacy of the function and role of pesantren Salaf like period once, without knowing that it is actually what is expected it is experiencing overcast condition and shrinkage. Expenses are given the added weight and more and more, but the ability to lift a boarding school in general was declining. Source overcast condition and depreciation mainly boils down to the weight and quality of the “clerics who brought up”. Both in terms of science, wisdom, exemplary, sincerity, and shelter to the people.